Implementation of Marketing Communication Strategy at Moju Moju Caffee & Tea by Utilizing Instagram as a Promotional Media - Pratama, Candra Ananda; Santoso, Budi (LEGAL BRIEF, 2024)
The development of coffee shops is trending and mushrooming, giving rise to tight business competition, therefore it is necessary to implement marketing communication strategies in developing and expanding market share. A marketing communication strategy is very necessary so that communication can be delivered accurately and effectively and can form awareness of customers or the general public in accordance with the goals to be achieved. The aim of this research is to find out how to implement marketing communication strategies on the Instagram account @mojumojuid in order to attract potential customers by utilizing the features available on the Instagram application to promote their products. This research uses descriptive qualitative methods through structured interview methods in collecting research data. There were eight respondents including one quality control, two baristas, and five customers around the Surakarta City area to obtain information and data in this research. The variable or theory used in the title of this research is an online marketing communication strategy with a communication mix approach based on advertising, sales promotion, events & experiences, public relations and publicity. ), direct marketing, interactive marketing, word of mouth promotion, personal selling and this theory can influence consumer decisions in using products